Analisis Kualitas Layanan Susi Air sebagai Operator Penerbangan Perintis di Luwu Utara - Fanggidae, Paulus Yulis; Kirani, Agnes Neisha; Melviana, Melviana (Universitas Batanghari Jambi, 2024)
Customer satisfaction is one of the main keys to determining the success of a business and its sustainability. Service businesses are business activities that require users to be in a